2006
DOI: 10.1291/hypres.29.493
|View full text |Cite
|
Sign up to set email alerts
|

Blocking T-Type Ca2+ Channels with Efonidipine Decreased Plasma Aldosterone Concentration in Healthy Volunteers

Abstract: Efonidipine can block both L-and T-type Ca2+ channels. In a previous in vitro study, we clarified that efonid-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…Efonidipine, another T-type CCB, has been shown to inhibit aldosterone synthesis and secretion in vitro, 9 as well as in both healthy subjects and patients with essential hypertension. 32,33 In this study, benidipine and amlodipine had no significant effect on clinic blood pressure, but both heart rate and plasma aldosterone level were significantly decreased in the benidipine treatment group. T-type CCBs inhibit renin secretion and renin gene expression in vivo, whereas L-type CCBs function as stimulators of the renin system.…”
Section: Discussionmentioning
confidence: 54%
“…Efonidipine, another T-type CCB, has been shown to inhibit aldosterone synthesis and secretion in vitro, 9 as well as in both healthy subjects and patients with essential hypertension. 32,33 In this study, benidipine and amlodipine had no significant effect on clinic blood pressure, but both heart rate and plasma aldosterone level were significantly decreased in the benidipine treatment group. T-type CCBs inhibit renin secretion and renin gene expression in vivo, whereas L-type CCBs function as stimulators of the renin system.…”
Section: Discussionmentioning
confidence: 54%
“…23,[29][30][31] Of interest, efonidipine possesses renal protective action via efferent arteriolar dilation, [17][18][19][20] the inhibition of Rho kinase 32 and, possibly, the inhibition of aldosterone activity. 33,34 Our present observations therefore imply a distinct therapeutic applicability of Ca channel blockers in CKD. 31,35 Of note, the present study showed that in patients with proteinuria at baseline, eGFR was lower than in non-proteinuric patients throughout the study period (Figures 4a and b, bottom).…”
Section: Discussionmentioning
confidence: 52%
“…In harmony with this, clinical studies in healthy subjects and hypertensive patients have shown that the acute or the chronic administrations of T-type CCB lower plasma aldosterone levels (39,40). We have compared the effects of L-and T-type CCB efonidipine and L-type CCB amlodipine in patients with glomerulonephritis and observed that efonidipine reduces plasma aldosterone concentration as compared with amlodipine while the plasma angiotensin II concentrations were comparable (Figure 10) (35).…”
Section: Calcium Channel Blockers In Antihypertensive Drug Therapy Fomentioning
confidence: 69%